Solution of Monkeypox transmission model using Picard Iterative Method - Khairuddin, Ahmad Bazli; Selamat, Mat Salim; Yacob, Nor Azizah (Universiti Teknologi MARA, Perak, 2025)
Monkeypox, an emerging zoonotic disease, has demonstrated human-to-human transmission, which necessitates detailed analysis of its spread dynamics. Mathematical modeling is crucial for understanding these dynamics, but the reliability of numerical methods used to solve such models can vary. This paper applies the Picard Iterative Method (PIM) to a monkeypox transmission model represented by an eight-dimensional system of nonlinear ordinary differential equations. This study introduces a novel approach that applies the Picard Iterative Method to solve the monkeypox transmission model. While earlier studies have focused on both integer-order and fractional-order models, this study uniquely emphasizes the application of PIM in infectious disease modeling. A comparative analysis with the classical fourth-order Runge-Kutta (RK4) method is presented. The results suggest that PIM provides reliable short-term predictions of monkeypox dynamics, offering valuable insights into outbreak patterns, and enhancing public health response strategies through improved numerical modeling approaches.